A Comprehensive Evaluation of Chinese Residents' Consumption Potential from 2010-2021 - Lyu, Wenbo; Chen, Haowen; Jiang, Yan; Feng, Jinsun; Huang, Tandang (Theoretical Key Issues and Practical Development Trends of China’s Digital Economy, 2024)
Household consumption holds significant importance within a nation's economy as one of its foremost constituents and serves as both a fundamental impetus for economic advancement and an ultimate objective. As China's socialist market economy continues to progress alongside improvements in living standards, there has been an expansion in Chinese residents' expenditure with enhancements made to its structure and quality while contributing increasingly towards economic growth annually. Consequently, household spending plays a pivotal role in our national economy. To foster sound progression in household spending necessitates implementing various measures such as elevating resident incomes, enhancing consumer environments, and bolstering market oversight amongst others; concurrently emphasizing comprehensive evaluations regarding resident spending potential will offer valuable insights for further enhancement.